1978
DOI: 10.1093/infdis/137.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Penicillinase-Producing Neisseria gonorrhoeae: Results of Surveillance in the United States

Abstract: In September 1976 the Center for Disease Control (Atlanta, Georgia) initiated surveillance for cases of infection due to penicillinase-productin Neisseria gonorrhoeae in the United States. One hundred ninety-one cases of penicillinase-producing gonococcal infection were confirmed through June 30, 1977. Of 177 cases for which histories of sexual exposure were available, 69 were traced to sexual contact in the Far East, and one was traced to sexual contact in West Africa. Of 181 cases for which clinical informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
10
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The older generation of cephalosporins, cephradine and cephalexin, was the least effective: 45 and 37% of the strains, respectively, required for inhibition MICs of -8 jig/ml. Cefotaxime, a new parenteral cephalosporin, was the most active; the median MIC was at least 10-fold lower than that of cefuroxime.The antibiotic susceptibility of Neisseria gonorrhoeae, and more recently of f8-lactamase-producing strains of N. gonorrhoeae isolated from many parts of the world, has been well documented (15,22,23 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The older generation of cephalosporins, cephradine and cephalexin, was the least effective: 45 and 37% of the strains, respectively, required for inhibition MICs of -8 jig/ml. Cefotaxime, a new parenteral cephalosporin, was the most active; the median MIC was at least 10-fold lower than that of cefuroxime.The antibiotic susceptibility of Neisseria gonorrhoeae, and more recently of f8-lactamase-producing strains of N. gonorrhoeae isolated from many parts of the world, has been well documented (15,22,23 …”
mentioning
confidence: 99%
“…The antibiotic susceptibility of Neisseria gonorrhoeae, and more recently of f8-lactamase-producing strains of N. gonorrhoeae isolated from many parts of the world, has been well documented (15,22,23 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The development of plasmid-mediated penicillin resistance in isolates of Neisseria gonorrhoeae (1,27,30), with its subsequent worldwide prevalence (35,36), has altered our perspectives on the acquisition of other plasmid-determined antibiotic resistances in gonococci and on the treatment of gonococcal infections. The monitoring and characterization of penicillinase production in N. gonorrhoeae has shown that the penicillinase plasmids are of two distinct sizes (28, 31) and that they are closely related to plasmids from the genus Haemophilus (10,38).…”
mentioning
confidence: 99%
“…These mechanisms are plasmid or chromosome encoded. The emergence of penicillinase-producing N. gonorrhoeae (PPNG) in 1976 has led to widespread high-level penicillin resistance (Ashford et al 1976, CDC 1976, Phillips 1976, Siegel et al 1978. Highlevel tetracycline resistance (MIC ³ 16 mg/ml) was reported for N. gonorrhoeae in 1985 by the Centers for Disease Control (CDC 1985).…”
mentioning
confidence: 99%